Improving vaccination coverage and timeliness through periodic intensification of routine immunization: evidence from Mission Indradhanush. Issue 1 (15th July 2021) - Summan, Amit; Nandi, Arindam; Deo, Sarang; Laxminarayan, Ramanan
Abstract: Only an estimated 62% of Indian children under the age of 2 years are fully immunized. We examined the association between India's Mission Indradhanush (MI)—a periodic intensification of the routine immunization program—which was implemented in phases across districts between March 2015 and July 2017, and routine vaccination coverage and timeliness among children. We used data from a 2015 to 2016 national survey of children ( n  = 29, 532) and employed difference‐in‐difference regressions to examine binary indicators of receipt of 11 vaccines and whether vaccines were received at recommended ages. The full immunization rate was 27% higher among children under 2 years old residing in MI phase 1 and 2 districts (intervention group) as compared with those residing elsewhere (control group). The rate of receiving all vaccines at recommended ages was 8% higher in the intervention group. Receiving doses of oral polio vaccine (OPV) birth dose, OPV dose 1 (OPV1), OPV2, OPV3, bacillus Calmette–Guérin, and hepatitis B birth dose vaccines were 9%, 9%, 11%, 16%, 5%, and 19% higher in the intervention group than the control group, respectively. More research is required on the cost‐effectiveness of investing in MI‐type programs as compared with routine immunization. Abstract : Only an estimated 62% of Indian children under the age of two years are fully immunized. We examined the association between India's Mission Indradhanush (MI)—a periodic intensification of the routine immunization program—which was implemented in phases across districts between March 2015 and July 2017, and routine vaccination coverage and timeliness among children.